Effect of 2–6 at.% Mo addition on microstructural evolution of Ti-44Al alloy. Issue 7 (July 2018) - Zhang, S.Z.; Song, Z.W.; Han, J.C.; Zhang, C.J.; Lin, P.; Zhu, D.D.; Kong, F.T.; Chen, Y.Y.
Abstract: In order to understand the effect of Mo alloying on the microstructural evolution of TiAl alloy, the as-cast microstructure, heat treated microstructure characteristic, and hot compression microstructure evolution of Ti-44Al alloy have been studied in this work. The as-cast microstructure morphology changes from ( γ +α2 ) lamellar colony and β / β 0 + γ mixture structure to β / β 0 phase matrix widmannstatten structure, when Mo content increases from 2 at.% to 6 at.%. Affected by the relationship between β phase and α phase, the angles between the lamellar orientation and the block β / β 0 phase are roughly at 0°, 45° and 90°. Comparing with heat treatment microstructure, the hot compression microstructure contains less β / β 0 phase, however, the β / β 0 phase containing 2Mo alloy and 3Mo alloy hot compressed at 1275 °C has the inverse tendency. In addition, (α2 + γ ) colony is decomposed by the discontinuous transformation.